Enhanced Production of Pterostilbene in Escherichia coli Through Directed Evolution and Host Strain Engineering - Yan, Zhi-Bo; Liang, Jing-Long; Niu, Fu-Xing; Shen, Yu-Ping; Liu, Jian-Zhong (Frontiers in Microbiology, 2021)
Pterostilbene is a derivative of resveratrol with a higher bioavailability and biological activity, which shows anti-oxidant, anti-inflammatory, anti-tumor and anti-aging activities. Here, directed evolution and host strain engineering were used to improve the production of pterostilbene in Escherichia coli. First, the heterologous biosynthetic pathway enzymes of pterostilbene, including tyrosine ammonia lyase, p-coumarate: CoA ligase, stilbene synthase and resveratrol O-methyltransferase, was successively directly evolved through error-prone PCR. Four mutant enzymes with higher activities of in vivo and in vitro were obtained. The directed evolution of the pathway enzymes increased the pterostilbene production by 13.7-fold. Then, a biosensor-guided genome shuffling strategy was used to improve the availability of the precursor L-tyrosine of the host strain E. coli TYR-30 used for the production of pterostilbene. A shuffled E. coli strain with higher L-tyrosine production was obtained. The shuffled strain harboring the evolved pathway produced 80.04 ± 5.58 mg/L pterostilbene, which is about 2.3-fold the highest titer reported in literatures.